The empowered patient on a historical-rhetorical model: 19th-century patent-medicine ads and the 21st-century health subject - Segal, Judy Z (Health (London, England : 1997), 2020)
The contemporary health subject, often described as a new, empowered patient, is not simply a character in a story of progress toward knowledge and power, away from credulity and passivity. Before the 20th century, and the assertion of a medical system that became frankly paternalistic, laypeople adjudicated on many matters of illness and its treatments. That is, 18th- and 19th-century health subjects were empowered too, and studying them, especially as consumers of health products, helps us develop a more nuanced account of our current medico-commercial selves. Comparing historical advertisements for “patent medicines” and contemporary direct-to-consumer ads for prescription pharmaceuticals, this essay contributes to such an account. It identifies strategies that drug marketers have deployed over centuries to persuade consumers to buy their products, and it tracks a rhetoric of interpellation in advertisements that not only address but also constitute health subjects. The goal of the analysis is to increase alertness to our own susceptibilities to pharmaceutical ads and adjacent rhetorics of health and illness.